Efficient signaling schedule for centralized and distributed scheduling algorithms for wimax multi-hop relay networks - Saqer, Ahmad Sabri Mousa (2012)
The Institute of Electric and Electronic Engineers (IEEE) 802.16j standard uses relay station to extend coverage and enhance throughput for remote users at the base station. The IEEE 802.16 standards specify services and how the transmissions should occur. However, the way how to run these services and when the transmission should be started are the task of scheduling algorithms which are not specified in the IEEE 802.16 standards. The IEEE standards left the design of scheduling algorithms open for the manufacturers. However, the scheduler is a very important component in wireless systems and the scheduling period presents the most common challenging issue in terms of time delay. This thesis presents new scheduling algorithms; centralized and distributed scheduling algorithms, for the WiMAX Multihop Relay (MR) Networks taking into account the bandwidth allocation signaling scheme for both the centralized and distributed scheduling modes. The proposed algorithms aim at making the MR network auto-configurable and flexible through reducing overhead and improving the network throughput. The proposed algorithms were also customized to produce signaling with less time delay over relay-link. In order to evaluate the proposed algorithms and validate their efficiency for IEEE 802.16j networks, the authors simulated the algorithms in QualNet simulator. Evaluation of the proposed centralized scheduling algorithm (MR-CSA) was carried out through comparing its performance with those of the Round Robin and the centralized pairing algorithms. On the other hand, the proposed distributed scheduling algorithm (MR-DSA) was evaluated by comparing its performance against performances of Greedy and the factor-graph-based low-complexity distributed scheduling algorithm (FGDS) algorithms in terms of delay, throughput, and overhead. Validation of the proposed algorithm (MR-CSA) was based on comparison of its performance with the performance of the centralized pairing algorithm while the proposed MR-DSA algorithm was validated through comparing its performance against that of the factor-graph-based low-complexity distributed scheduling algorithm (FGDS) algorithms in terms of throughput and the average packet throughput. The simulation results highlighted that the proposed algorithms (MR-CSA and MR-DSA) outperform all previous algorithms with the current signaling scheme. The proposed algorithms achieve higher performance in terms of end-to-end delay, throughput, overhead, link utilization, and fairness index than all other algorithms.